EFEKTIFITAS PERMAINAN BONEKA JARI UNTUK MENINGKATKAN KEMAMPUAN PENGURANGAN BILANGAN BULAT BAGI ANAK TUNAGRAHITA X - Oki Yosastra, Yosfan Azwandi, Asep Ahmad Sopandi (Universitas Negeri Padang, 2013)
The research was motivated by problems that occur mentally retarded DVI class C in SLB Bina Bangsa Padang with difficulties in completing operations reduce the number 1 to 10. This study aims to prove the effectiveness of finger puppets games to enhance operational capabilities integer reduction for mentally retarded. Research using methods Single Subject Research (SSR) with ABA design and data analysis techniques using graphic visual analysis. The results showed that, the capabilities of the mentally retarded integer operations increased reduction.